The call [videorecording (DVD)] - Anderson, Brad, 1964-; Berry, Halle; Chestnut, Morris; Breslin, Abigail, 1996- (Columbia : [Distributed by] Sony Pictures Home Entertainment, 2013)
When a veteran 911 operator takes a life-altering call from a teenage girl who has just been abducted, she realizes that she must confront a killer from her past in order to save the girl's life.